Peripherally Administered Y2-Receptor Antagonist BIIE0246 Prevents Diet-Induced Obesity in Mice With Excess Neuropeptide Y, but Enhances Obesity in Control Mice - Ailanen, Liisa; Vähätalo, Laura H.; Salomäki-Myftari, Henriikka; Mäkelä, Satu; Orpana, Wendy; Ruohonen, Suvi T.; Savontaus, Eriika (Frontiers in Pharmacology, 2018)
Neuropeptide Y (NPY) plays an important role in the regulation of energy homeostasis in the level of central and sympathetic nervous systems. Genetic silencing of peripheral Y2-receptors have anti-obesity effects, but it is not known whether pharmacological blocking of peripheral Y2-receptors would similarly benefit energy homeostasis. The effects of a peripherally administered Y2-receptor antagonist were studied in healthy and energy-rich conditions with or without excess NPY. Genetically obese mice overexpressing NPY in brain noradrenergic nerves and sympathetic nervous system (OE-NPY(DβH)) represented the situation of elevated NPY levels, while wildtype mice represented the normal NPY levels. Specific Y2-receptor antagonist, BIIE0246, was administered (1.3mg/kg/day, i.p.) for 2 or 4½ weeks to OE-NPY(DβH) and wildtype mice feeding on chow or Western diet. Treatment with Y2-receptor antagonist increased body weight gain in both genotypes on chow diet and caused metabolic disturbances (e.g. hyperinsulinemia and hypercholesterolemia), especially in wildtype mice. During energy surplus (i.e. on Western diet), blocking of Y2-receptors induced obesity in wildtype mice, whereas OE-NPY(DβH) mice showed reduced fat mass gain, hepatic glycogen and serum cholesterol levels relative to body adiposity. Thus, it can be concluded that with normal NPY levels, peripheral Y2-receptor antagonist has no potential for treating obesity, but oppositely may even induce metabolic disorders. However, when energy-rich diet is combined with elevated NPY levels, e.g. stress combined with an unhealthy diet, Y2-receptor antagonism has beneficial effects on metabolic status.